Faktor Pemicu Praktik Tax Avoidance - Dansen Yino; Andreas Bambang Daryatno (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2026)
The purpose of this research is to provide evidence regarding the effect of transfer pricing, capital intensity, leverage and profitability on tax avoidance in mining companies listed on the Indonesia Stock Exchange (IDX) for the period of 2022 to 2024. This research used sixty nine company samples with a purposive sampling method. This research using secondary data in the form of financial statement of the company. Data processing using EViews 13 software. The result of this research show that transfer pricing has no effect on tax avoidance, capital intensity and profitability has a positive effect on tax avoidance and leverage has a negative effect on tax avoidance. The implication of this research is that the government can review the existing regulations so that tax avoidance is not carried out excessively.